Сучасні тенденції у використанні мов програмування для розробки програмного забезпечення в метрології - Юношев, Д. Є. (ХНУРЕ, 2024)
In the modern world, metrology has become an increasingly important field as accuracy and measurement impact various aspects of our lives, including science, industry and technology. Metrology software development plays a key role in ensuring accurate and reliable measurements. This raises the question of choosing programming languages to create highly efficient and innovative solutions. The dissertation examines current trends in the use of programming languages for software development in metrology and their impact on the productivity and development of this industry
Keywords: метрологія; програмне забезпечення в метрології